Travellers' Perception on Travel Service Providers in an Electronic Environment - Ravichandran, K. (Indian Journal of Marketing, 2008)
Travel and tourism researchers have emphasized the increasing role of internet in the industry. For tourism suppliers, the internet provides an avenue to market and sell their products globally to potential customers. On the other hand it offers information on travel destinations, booking sources, ticketing and other travel related services. Thus it has emerged as a major source of information, access and buying point for travelers which can all be done at their own pace and convenience. In light of this, the perception of travelers and their views on travel agencies and tour operators and an understanding of this critical issue from different dimensions are crucial for formulating appropriate marketing strategies for both online and traditional businesses. The paper mainly highlights the question of disintermediation by the internet in travel trade by respondents who have purchased online as well as those who have not purchased online. Moreover, it also probes whether long haul and short haul travelers rely on travel websites or more on travel professionals who offer a human interface in travel related services. It concludes with discussions on the implications for both online and traditional travel businesses.